Effect of Manuka Honey Eye Drops among Patients Diagnosed with Adenoviral Keratoconjunctivitis in The Gaza Strip - Aysha F. Alagha; Riad El-Qidra; Marwan O. Jalambo; Bassam Alhabibi (Proceedings, 2023)
A large amount of research has established that honey has potent antibacterial activity. However, the sensitivity of infection-causing viral species to honey has been scarcely studied. This study was designed to evaluate the effect of Manuka Honey eye drops among patients diagnosed with adenovirus conjunctivitis. Sixty-one patients with adenovirus keratoconjunctivitis were recruited in this quasi-experimental, multi-center study. All eligible subjects were randomly categorized into two groups: the first group was the control group, which was treated with steroids (conventional treatment), while the second group was the intervention group, which was treated with Manuka Honey drops at a concentration of 16.5% four times per day with conventional treatment (steroids). Symptoms in both groups, as well as the total ocular symptom score (TOSS), were compared. The results of the experimental group demonstrate the effectiveness of Manuka Honey eye drops in relieving symptoms of adenovirus keratoconjunctivitis. The findings of this study indicated that there was a statistically significant difference between the groups in terms of the number of days they had adenovirus keratoconjunctivitis (p > 0.001). Also, the mean itchy, redness, and tearing scores on day 4 among the patients in the intervention group were less than those in the control group (p > 0.001). In addition, the TOSS score on day 4 and day 8 among the patients in the intervention group was extremely lower than those in the control group (p > 0.001). The results of this study have shown important improvements in the symptoms of adenovirus keratoconjunctivitis. Our findings showed positive results within a short period, meaning that our results suggest that Manuka honey eye drops show promise as an adjunct natural treatment and that prescribing them in conjunction with conventional steroids can help alleviate the symptoms of adenovirus keratoconjunctivitis.